Mineral metabolism of pregnant goats under feed restriction - Harter, Carla J. [UNESP]; Lima, Lisiane D. [UNESP]; Castagnino, Douglas S. [UNESP]; Rivera, Astrid R. [UNESP]; Nunes, Alana M. [UNESP]; Sousa, Samuel F. [UNESP]; Liesegang, Annette; Resende, Kleber T. [UNESP]; Teixeira, Izabelle A. M. A. [UNESP] (Csiro Publishing, 2017)
We examined the effects of feed restriction on calcium, phosphorus, magnesium, sodium and potassium metabolism in Oberhasli and Saanen goats during gestation. The 63 goats were distributed into groups that were divided into three levels of feed restriction (0%, 20% and 40% restriction) and slaughtered at different pregnancy stages (80, 110 and 140 days of gestation), in a randomised block design with a 2 x 3 x 3 factorial arrangement. The mineral balance was determined at similar to 80, 110 and 140 days of gestation. The serum levels of minerals and alkaline phosphatase activity were determined during pregnancy. Mineral retention in the maternal body, femur, empty uterus, mammary gland, fetus and fetal fluid was also determined during gestation. Bone mineral density was measured in the femur. Mixed models with days of gestation, levels of feed restriction, breed and their interactions as fixed effects and blocks as random effect were used for data analysis. In response to the reduction in feed intake, the maternal body uses its mineral reserves to maintain gestation. Physiological adjustments of the goats subjected to 20% feed restriction avoided a decrease in fetal mineral deposition. More severe feed restriction, however, compromised concentrations of phosphorus, sodium and potassium in the fetus, which were the main minerals used by the maternal body, whereas calcium and magnesium deposition in fetuses remained unaffected. At 40% feed restriction, the retention of all minerals in the body decreased, and the fetal dry mass was on average also less than those fetuses from goats without feed restriction. The fetal deposition of phosphorus, sodium and potassium was also lower during 40% restriction.
Keywords: gestation; fetal mineral deposition; maternal body; mineral retention; undernutrition